ECONOMETRIC ANALYSIS OF ATTRACTING INVESTMENTS TO SPECIAL ECONOMIC ZONES IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
An econometric analysis of attracting investments to special economic zones is presented in the article. Also, an econometric study was carried out to sort out the factors and explain them, to build an econometric model that shows the level of interdependence and the level of influence of the factors affecting the volume of investment in special economic zones.